Odpowiedzi

Najlepsza Odpowiedź!
2010-02-23T19:00:27+01:00
(a-1)³ = a³ - 3a² +3a - 1
(2+b)³ = 8 + 12b + 6b² + b³
(3a+1)³ = 27a³ + 27a² + 9a + 1
(m+5)³ = m³ + 15m² + 75m + 125
(n-2a)³ = n³ - 6an² + 12a²n - 8a³
(3x+5y)³ = 27x³ + 135x²y + 225xy² + 125y³
(x-4y)³ = x³ - 12x²y + 48xy² - 64y³
2010-02-23T19:12:38+01:00
(a-1)³=a3-3a2=3a-1
(2+b)³= 23=3=3*22b=3*2*b2=b3=6=3*4b=6b2=b3=6=12b=6b2=b3
(3a+1)³=3a3=3*3a2=3*3a=1=3a2=9a2=9a=13a2=9a=1
(m+5)³=m3=3*m2*5=3*m*25-125=m3=15m@=75-125
(n-2a)[email protected]=3n2a2-2a3
(3x+5y)³=3x#=3*3x2*5y=3*3x*5y2=5y3=3x3=135x2y=135xy2=5y3
(x-4y)³=x3-3*x2*4y+3x*4y2-4y3=x3-12x2y=12xy2-4y2
x3 x2 y2 y3- to potęgi